Partisipasi Aktif Masyarakat dalam Proses Pemberdayaan: Studi Kasus di Kota Dumai - Jannah, Dewi (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
: This study investigates community empowerment in Dumai, focusing on active participation as a key element. Challenges such as educational inequality, economic uncertainty, limited access to information, and uneven healthcare services are identified as barriers to optimal participation. The research proposes solutions and opportunities for improvement, including strengthening non-formal education, promoting local economic development, leveraging Information and Communication Technology (ICT), and expanding community healthcare services. Drawing on case studies and scholarly insights, the study suggests that investing in these areas can foster community engagement and empowerment. Recommendations encompass enhancing educational accessibility, addressing economic uncertainties through small business development, utilizing ICT for information dissemination, and ensuring equal access to healthcare services. Collaborative efforts involving government, private sectors, and local communities are crucial for implementing effective strategies. This research contributes to the discourse on community empowerment, providing a framework for tailored interventions in Dumai and potentially serving as a model for other communities facing similar challenges.